Desensitization of TRPA1 by dimethyl itaconate attenuates acute and chronic pain in mice - Xu, Sen; Zhao, Jia-Yue; Ma, Jun-Yi; Cui, Xia-Lin; Lin, Jia-Hui; Sun, Shi-Yu; Liu, Si-Jia; Zhou, Guo-Kun; Zhang, Jiang-Tao; Kang, Peipei; Liu, Tong (Frontiers in Pharmacology, 2025)
IntroductionChronic pain remains a significant clinical challenge due to the limited efficacy of current analgesics. Dimethyl itaconate (DMI), a cell-permeable derivative of itaconate with known anti-inflammatory and immunomodulatory properties, has recently shown promise in alleviating pain. However, the mechanisms by which DMI modulates acute and chronic pain remain unclear.MethodsCalcium imaging was employed to assess the activation and desensitization effects of DMI on TRPA1 in hTRPA1-HEK293T cells and DRG neurons. Molecular docking analysis was conducted to evaluate the potential covalent binding sites between DMI and TRPA1. Behavioral assays were used to establish acute and chronic pain models in mice and to examine the analgesic effects of DMI in these models.ResultsIn the present study, we found that DMI directly activates and desensitizes the transient receptor potential ankyrin 1 (TRPA1) channel, a critical calcium-permeable ion channel implicated in various pain states. Molecular docking analysis and functional assays using calcium imaging revealed possible covalent interactions between DMI and key TRPA1 residue (cysteine 621). To further explore the possible therapeutic effects of DMI for chronic pain, we investigated the possible analgesic effects of DMI in multiple chronic pain mouse models. Single intraplantar injection of DMI induced transient mechanical hypersensitivity in a dose-dependent manner, while repeated injection of DMI failed to induce pain responses in mice. Furthermore, repeated intraperitoneal administration of DMI alleviated pain-related behaviors in a variety of acute pain models, including allyl isothiocyanate (AITC)- and formalin-induced acute inflammatory pain. Moreover, DMI alleviated pain-related behaviors in chronic pain models, including dextran sulfate sodium (DSS)- induced colitis, complete Freund’s adjuvant (CFA)-induced inflammatory pain, oxaliplatin-induced neuropathic pain, and bone cancer pain in mice. Finally, the anti-hyperalgesia effects of DMI on CFA-induced inflammatory pain was abolished in TRPA1 knockout mice.DiscussionTogether, our findings demonstrate that DMI acts as a novel TRPA1 agonist for attenuating acute and chronic pain, possible through TRPA1 desensitization. Thus, DMI may be further developed as a potential therapeutic strategy for the treatment of acute and chronic pain.